Serum levels of bone formation and resorption markers in relation to vitamin D status in professional gymnastics and physically active men during upper and lower body high-intensity exercise - Mieszkowski, J.; Kochanowicz, A.; Piskorska, E.; Niespodzinski, B.; Siódmiak, J.; Busko, K.; Stankiewicz, B.; Olszewska-Slonina, D.; Antosiewicz, J. (Journal of the International Society of Sports Nutrition, 2021)
Purpose/introduction: To compare serum levels of bone turnover markers in athletes and non-athletes, and to evaluate the relationship between serum levels of vitamin D metabolites and exercise-induced changes in biomarker levels. Methods: Sixteen elite male artistic gymnasts (EG; 21.4 ± 0.8 years-old) and 16 physically active men (the control group, PAM; 20.9 ± 1.2 years-old) performed lower and upper body 30-s Wingate anaerobic tests (LBWT and UBWT, respectively). For biomarker analysis, blood samples were collected before, and 5 and 30 min after exercise. Samples for vitamin D levels were collected before exercise. N-terminal propeptide of type I collagen (PINP) was analysed as a marker of bone formation. C-terminal telopeptide of type I collagen (CTX) was analysed as a marker of bone resorption. Results: UBWT fitness readings were better in the EG group than in the PAM group, with no difference in LBWT readings between the groups. UBWT mean power was 8.8% higher in subjects with 25(OH)D3 levels over 22.50 ng/ml and in those with 24,25(OH)2D3 levels over 1.27 ng/ml. Serum CTX levels increased after both tests in the PAM group, with no change in the EG group. PINP levels did not change in either group; however, in PAM subjects with 25(OH)D3 levels above the median, they were higher than those in EG subjects. Conclusion: Vitamin D metabolites affect the anaerobic performance and bone turnover markers at rest and after exercise. Further, adaptation to physical activity modulates the effect of anaerobic exercise on bone metabolism markers.